Exosomes as mediators of intercellular crosstalk in metabolism - Isaac, Roi; Reis, Felipe Castellani Gomes; Ying, Wei; Olefsky, Jerrold M. (Cell metabolism, 2021)
Exosomes are nanoparticles secreted by all cell types and are a large component of the broader class of nanoparticles termed extracellular vesicles (EVs). Once secreted, exosomes gain access to the interstitial space and ultimately the circulation, where they exert local paracrine or distal systemic effects. Because of this, exosomes are important components of an intercellular and intraorgan communication system capable of carrying biologic signals from one cell type or tissue to another. The exosomal cargo consists of proteins, lipids, miRNAs, and other RNA species, and many of the biologic effects of exosomes have been attributed to miRNAs. Exosomal miRNAs have also been used as disease biomarkers. The field of exosome biology and metabolism is rapidly expanding, with new discoveries and reports appearing on a regular basis, and it is possible that potential therapeutic approaches for the use of exosomes or miRNAs in metabolic diseases will be initiated in the near future. Exosomes are intercellular and intraorgan communication components with similarities to a classical endocrine system. In this review, Isaac and Reis et al. discuss basic aspects of exosome biology and the role of exosomes in metabolic homeostasis including their potential use as therapeutic agents.